(untitled) (Revista de Ciências Agroveterinárias, 2016)
The significant growth and regional concentration of swine farming in Brazil also increases the risk of soil and water pollution by excessive pig slurry (DLS) applied to crops. The impact of DLS application on the contents of elements in the subsoil soil solution of a southern Brazil Oxisol under different doses of this waste was evaluated in a field experiment. The treatments were annual applications of DLS in the: 0, 50, 100 and 200 m³ ha-1; soluble mineral fertilizer (AM); and DLS combined with AM (DLS + AM) which were organized in the complete block design with four replicates. The mineral N, P, K, Ca and Mg contents were determined in soil solution extracted through lysimeter suctions placed at 0.4 and 0.8 m depths during the 13th year after the start of applications. The N-NH4+ content in soil solution were higher with the doses 100 and 200 m³ ha-1 of DLS and this also happened to the soluble N application in coverage. The dose 200 m³ ha-1 also promoted greater concentration of N-NO3- than the other treatments. The N-NH4+ content was lower than the N-NO3- content, although this form occurs in less content in the DLS. The P content in soil solution was below the method detection limit, indicating that there was no excess of that nutrient in the solution extracted at the depths evaluated. The K+, Ca2 + and Mg2 + contents in the soil solution increased with the high doses of DLS, showing that prolonged use of this waste promotes the movement of these basic cations to lower layers of the soil profile. The high dosages of DLS applied increase losses of N in the form of nitrate and basic cations (K+, Ca+ 2 and Mg+ 2) by leaching.